POLIGAMI SEBAGAI SOLUSI DALAM MENSEJAHTERAKAN WANITA DI DESA AIR SEBAYUR KECAMATAN PINANG RAYA KABUPATEN BENGKULU UTARA - Marviawan, M; Baehaqi, B; Syamsuddin, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The main problem studied in this research are 1. Womens problem which are very complex, including the many women who are displaced and need protection, girls who haven’t got husbands, widows who weak materially, orphans who need help. 2. Who the practice of polygamy in Air Sebayur, Pinang Raya, North Bengkulu is able to provide solutions in the welfare of women.The purpose of this research is 1. To analyze the practice of polygamy in Air Sebayur, Pinang Raya, North Bengkulu. 2. To analyze the positive impact of polygamy which is able to provide solutions for the walfare of women. This research uses field research, namely direct research in to the field where researchers visit research objects. Collecting data by conducting direct intrviews, observation and documentation. The data used are primary data and secondary data. Data analysis used individual site data analysis tecniques (individual-site analysis) and cross site analysis (cross-site analysis). To test validity of data, it is done trought credibility, transferability, dependability, and confirmability. The results of this research indicate that: Poligamist in practicing their polygamy based on Islamic law and invitation law number 1 of 1974 with the provisions: Get approval and permission from the wife, the number is limited to only four women, able to act fairly towards the wife and childrens, get permission from religious court. So that it became a happy and harmonious and happy family be a solution in the welfare of women.